Philosophical Analysis Of The Influence Of International Migration On The Process Of Intercultural Communication (Zien Journal of Social Sciences and Humanities, 2025)
Intercultural communication is private or public communication between representatives of different human cultures. As a result of migration, the situation of international intercultural communication will increase. This article philosophically analyzes the influence of migration types on the material communication of humanity and the transformation of values.